A Review: The Effect of Emotional Intelligence, Spiritual Intelligence, Love of Money and Ethical Sensitivity on Students’ Ethical Perceptions Regarding the Code of Ethics for the Accountant Profession - Susilawati Desi; Diwanti Dyah Pikanthi; Turidho Resma Kurnia; Polanunu Ummul Ulya; Nuryaningrum Aninda (SHS Web of Conferences)
The present study analyzes the effect of emotional intelligence, spiritual intelligence, love of money, and ethical sensitivity on students’ ethical perceptions regarding the code of ethics of the accounting profession. This research uses a quantitative method with secondary data and employs the purposive sampling technique from a population of students who have taken auditing courses. The number of samples used in this research was 106 respondents. The obtained data was evaluated using a multiple linear regression analysis. This research’s findings indicate that emotional intelligence, spiritual intelligence, and ethical sensitivity positively influence students’ ethical perceptions regarding the accounting profession’s code of ethics. Conversely, having a love-for-money mindset has a negative impact on students’ moral understanding of the code of ethics in the accounting profession. The factors that influence the ethical perception of the code of ethics are emotional intelligence, intellectual intelligence, and love of money. Low levels of love of money tends to work less satisfactorily. Even the level of love of money also affects unethical behavior. Unethical behavior can be fortified with religious intelligence and fear of God Almighty.